The Commonalities of Socially Responsible Investment With Islamic Finance: A Bibliometric Analysis - Muttaqin, Ecky Imamul (Universitas Islam Internasional Indonesia, 2024)
This study aims to evaluate the number of overviews on the commonalities of socially responsible investment (SRI) with Islamic finance by providing critical thinking in terms of the investment screening process. The main critical reviews are obtained from the articles, paperwork, and previous related studies from reputable open access journals such as Emerald, SSRN databases, and other indexed-Scopus on the Web of Science. This study finds that the commonalities of socially responsible investment with Islamic finance has seemingly been characterized as a slow-moving but unstoppable works since global movements aspire to prevent a transgression of Earth's boundaries towards financial risks. Intertemporal choice accounts for how reliable constitutes for transitioning and adapting planetary boundaries in investment decisions. The challenge is to bridge the postulated gap on the commonalities of SRI with Islamic finance leading into social and financial return aspects in order to construct long-term predictions and scenarios embodying the Islamic finance concept through environmental, social and governance (ESG) approach.